2017
DOI: 10.1016/j.jfma.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Self-harm and its association with internet addiction and internet exposure to suicidal thought in adolescents

Abstract: Online experiences are associated with SH in adolescents. Preventive strategies may include education to increase social awareness, to identify the youths most at risk, and to provide prompt help.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 32 publications
2
54
0
7
Order By: Relevance
“…Lam et al (11) suggested that Internet addiction is detrimental to mental health and increases the risk of NSSI among adolescents. Consistent with this observation, when controlled for gender, family factors, exposure to suicidal thoughts in real life, depression, alcohol/tobacco use, concurrent suicidality, and perceived social support, both internet addiction and exposure to suicidal thoughts on the internet were significantly related to an increased risk of NSSI (12). A systematic review suggested a relationship between internet use and NSSI; NSSI was associated particularly with internet addiction, high levels of internet use, and visiting websites related to self-injury or suicide (13).…”
Section: Introductionsupporting
confidence: 62%
“…Lam et al (11) suggested that Internet addiction is detrimental to mental health and increases the risk of NSSI among adolescents. Consistent with this observation, when controlled for gender, family factors, exposure to suicidal thoughts in real life, depression, alcohol/tobacco use, concurrent suicidality, and perceived social support, both internet addiction and exposure to suicidal thoughts on the internet were significantly related to an increased risk of NSSI (12). A systematic review suggested a relationship between internet use and NSSI; NSSI was associated particularly with internet addiction, high levels of internet use, and visiting websites related to self-injury or suicide (13).…”
Section: Introductionsupporting
confidence: 62%
“…The prevalence of IA in the present Turkish sample (17.7%) is higher than that of China (11%) [Lam et al 2009], Australia (10.8%) [Choi et al 2009], Greece (8%) [Siomos et al 2009], Taiwan (17.1%) [Liu et al 2017] and the USA (9%) [Caplan 2007]. Moreover, IA affects approximately 1.2% to 26.3% of U.S. university students [Li et al 2015].…”
Section: Discussionmentioning
confidence: 57%
“…In a recent systemic review, IUDs were found to be significantly related to both non-suicidal self-harm and suicidality [46]. In a Taiwanese study of 2479 high school students, both IUD and online exposure to suicidal content increased the risk of selfharm prior to adjustment for levels of self-esteem in participants, while only online exposure to suicidal content remained statistically significant following adjustment [47]. This important finding suggests the potential mediating role of harmful content to negative consequences of IUDs.…”
Section: Harmful Contentmentioning
confidence: 99%